Morpho-physiological evaluation of Pfaffia glomerata (Spreng.) Pedersen accessions grown under photoautotrophy and water stress conditions - Chagas, Kristhiano (2019)
This study aimed to evaluate the morpho-physiological aspects of Pfaffia glomerata (Spreng.) Pedersen accessions grown under photoautotrophy and water stress conditions. In order to address that three experiments were conducted. In the first experiment, diploid (Ac 04, 22 and 43) and synthetic polyploid (Poly 28, 60, 68 and 74) accessions of P. glomerata were grown in vitro under photoautotrophy on a sugar-free MS-based medium, using cellulose and vermiculite (1:2 ratio) as supporting material, and maintained in a growth room at 25 ± 2°C and 60 μmol m -2 s -1 irradiation, provided by red/blue led lamps for 30 days. In the second experiment, two P. glomerata accessions (Ac 22 and 43) propagated in vitro were acclimatized in a greenhouse and submitted to moderate and severe water deficit for 15 days, after 7 days were rehydrated and performed analysis in conditions stressed and recovery. In the third experiment, the effects water deficit elicited in vitro by supplementing a MS-based medium withof polyethyleneglycol (PEG 6000) at 0, 0.1, 0.2, 0.3%) evaluated by comparing plants grown for 20 days under stress and after 7 days rehydration. Here, a versatile light chamber formed by 8 high brightness white LEDs disposed on the inside wall of an expanded polystyrene (EPS) box and used with source photosynthetic photon flux (600 μmol m -2 s -1 ) in measurements of photosynthesis in vitro. Under photoautotrophic conditions, the polyploids exhibited lower leaf number, and thicker and more expanded leaves, increased stomata size and reduced stomata density compared to the diploid counterparts. Even with the morphological differences, all assayed accessions showed average in vitro photosynthetic rate of 7.31 μmol m -2 s -1 and Fv/Fm 0.79. The Ac 04 presented and 20-hydroxyecdysone (20E) contents. The drought stress led to a marked decrease in biomass, height, leaf expansion, epidermis and mesophyll, and increased stomatal density, for both accessions (Ac 22 and Ac 43) raised in vitro and ex vitro. The photosynthetic rate and dark respiration increased in stressed plants in greenhouse, whereas the addition of PEG in vitro decreased photosynthesis. On topo of that, the water deficit led to increased contents of abscisic and salicylic acid, stimulated antioxidant enzyme activities, and osmoregulatory status, but to a decreased zeatin levels. The Ac 43 maintained under full irrigation exhibit higher content and field yield of 20E than Ac 22, both accessions the water deficit in greenhouse and in vitro increased 20E levels and decrease in production total of metabolite. This work proposes an innovative, practical and efficient LED-based apparatus to efficiently evaluate the photosynthetic rates of vitroplants, thus providing foundations to expand the understanding of the acquisition of photosynthetic competence during plant development under photoautotrophic in vitro environment. These findings also provide a better understanding of the different morpho-physiological responses of synthetic polyploids P. glomerata under photoautotrophy, and acclimation strategies adopted by the species that enable drought tolerance and pave the way for further studies that can lead to improved 20E production, a bioactive compound with high economic value and biochemical interest. Keywords: Light source; gas exchange; synthetic polyploidy; Brazilian ginseng; 20- hydroxyecdysone; endogenous hormone levels; water stress